Aglossa mayrae Ylla, Sumpich, Gastón, Huertas & Macià, sp. n., a new species from Spain (Lepidoptera: Pyralidae, Pyralinae) - J. Ylla; J. Sumpich; F. J. Gastón; M. Huertas; R. Macià (SHILAP, 2017)
Aglossa mayrae Ylla, Sumpich, Gastón, Huertas & Macià, sp. n. is described from various localities in southeast Spain. The differences between morphologically similar species of genus Aglossa Latreille, 1796 inhabiting the Iberian Peninsula are given as well as photographs of the adults and their genitalia.